WOOD COLOUR MODIFICATION OF FRAXINUS EXCELSIOR L. DURING THE PROCESS OF THERMAL TREATMENT WITH SATURATED WATER STEAM - Dzurenda, Ladislav; Banski, Adrián (Innovation in Woodworking Industry and Engineering design, 2018)
The aim of the paper is to determine the colour of European ash wood (Fraxinus excelsiorL.) in the CIE-L*a*b* colour space during the thermal treatment with saturated water steam at the temperature of t = 137.5 ± 2.5 °C for the time of τ = 7.5 hours. The colour of European ash wood changes from white with a yellow hue to brown during the process of colour modification. Mentioned hue of thermally modified wood is described with the coordinates of CIE-L*a*b*colour space: L* 65.6 ± 1.4; a* = 10.8 ± 0.5; b* = 21.7 ± 0.9. Irreversible colour change of the European ash wood resulting from the process of thermal modification with saturated water steam widen the possibility for its use in the field of construction and carpentry, design as well as in the field of art.